FACTORS THAT AFFECTING FIRM VALUE - Aurelia, Aurelia; Prajitno, Sugiarto (E-Jurnal Akuntansi TSM, 2024)
The research objectives is to obtain empirical evidence about factors that affect firm value, current ratio, return on asset, debt to asset ratio, investment decision, dividend policy, firm size, and corporate social responsibility on firm value. The population that is used in this research are all companies from the consumer cyclicals and consumer non-cyclicals industry listed in the Indonesia Stock Exchange from 2020 to 2022 and apply purposive sampling as the sampling method. With this method, it is obtained that thirty seven (37) companies from the consumer cyclicals and consumer non-cyclicals industry. This research uses multiple regression method to analyze the data.The results obtained from multiple regression show that the independent variables, namely return on asset and debt to asset ratio has an influence on firm value. Meanwhile, other independent variables, namely current ratio, investment decision, dividend policy, firm size, and corporate social ressponsibility have no influence on firm value